Temperature anisotropy relaxation processes in dense plasma - Ramazanov, T.S.; Kodanova, S.K.; Issanova, M.K.; Orazbayev, S.A.; Yelubaev, D.Ye. (Recent Contributions to Physics, 2020)
In this work the relaxation processes of dense plasmas were studied. The relaxation rate of a Maxwellian velocity distribution function that has an initially anisotropic temperature (T∥ ≠ T^) is an important physical process inertial confinement fusion plasmas. Relaxation characteristics in dense plasmas were studied on the basis of the effective potentials using the Coulomb logarithm. The effective potential is derived using the long wavelength expansion of the polarization function and quantum potential which takes into account the finite value of the interaction potential at close distance. In presented work temperature anisotropy relaxation processes in dense, non-isothermal plasma are considered. These interaction potential between particles take into account such collective effects as the ionization energy depression (reduction) and exchange-correlation effects. Therefore, this allowed us to examine the sensitivity of the computed relaxation time and the corresponding equilibrium plasma temperature on the quality of the description of the screening effect in dense plasmas.